Stories through seams safeguarding Intangible Cultural Heritage (ICH) through the Aklan Pina Weaving Creative and Innovation Center - Baja, Sofia Isabel S.; Simoun T. Ong (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
With each woven thread, the story of a community unfolds -- a story now threatened by time and disinterest. As the weavers age and the youth turn back on continuing the tradition, Aklan pina handloom weaving is at a decline of workers, endangering the future of the craft. This comprehensive design project investigates how architecture can address safeguarding this intangible cultural heritage while capturing the interest of younger generations. Phenomenological research through site visits and in-depth interviews was carried out to probe the current state of the practices, technologies, and heritage education and preservation in the industry, and desk research was done to look into how foreign studies promote their intangible cultural heritage which could be adapted in the Philippine context. Findings show that innovations are currently being done in the industry such as experimenting media and textile materials in weaving fabric, and exploring how to automate labor-intensive process. This could be further improved through incorporating technology with digital archiving and teaching methods. This study highlights community-oriented and immersive design through providing spaces such as traditional working studios, a digital museum, and an innovation workshop. Once a symbol of colonial power, Spanish Red pineapple was transformed by weavers into cloth exuding elegance and premium quality, now serving as a beacon of Filipino identity. Creating weaving-related spaces cascades impact down to those from the grassroots, as weavers work closely with people such as farmers.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Handlooms -- Aklan; Intangible property -- Aklan; Cultural property -- Preservation -- Aklan